Analysis of the Implementation of the 1000 HPK Program Policy in Stunting Prevention - Winda, Winda; Eliska, Eliska; Gurning, Fitriani Pramita (Indonesian Journal of Global Health Research, 2024)
In the 2021 Indonesian Nutritional Status Study, there are 5 districts/cities with the highest stunting in the province of North Sumatra, namely South Tapanuli, Padang Lawas, Mandailing Natal, Pakpak Bharat, Tapanuli Tengah, Asahan Regency ranked 15th out of 33 City Districts. Stunted toddlers at the Meranti Health Center will experience an increase of 7 cases in 2022 to 8 cases in 2023. This research aims to analyze the implementation of the 1000 HPK program policy at the Meranti Health Center. Descriptive qualitative research method carried out in March 2023. Research informants include the Head of the Meranti Community Health Center, Nutrition Coordinator, KIA Coordinator, Promkes Coordinator, Cadres and Mothers of Stunting Toddlers. Data were collected using observation, in-depth interviews and documentation studies. The results of research on the input of inadequate human resources and facilities/infrastructure at the Meranti health center. In the process, ANC examinations, monitoring the growth of toddlers, providing immunizations, PMT, and counseling on stunting have gone well, although there are obstacles in their implementation. In terms of output, many programs have achieved targets. However, it is necessary to increase programs to prevent stunting so that they can be maximized.